Physiological movement disorder-like features during typical motor development. (July 2018) - Kuiper, M.J.; Brandsma, R.; Vrijenhoek, L.; Tijssen, M.A.J.; Burger, H.; Dan, B.; Sival, D.A.
Abstract: Aim: To compare physiological age-relatedness between dyskinesia (dystonia/choreoathetosis), dystonia and ataxia rating scale scores in healthy children. Method: Three movement disorders specialists quantified dyskinetic-like features in healthy children (n = 52; 4–16 years) using the Dyskinesia Impairment Scale (DIS = DIS-choreoathetosis (DIS-C) + DIS-dystonia (DIS-D)). We compared the age-related regression coefficients of the DIS with data processed from previous studies on dystonia and ataxia rating scales (Burke-Fahn-Marsden Movement and Disability Scales (BFMMS and BFMDS) and Scale for Assessment and Rating of Ataxia (SARA), International Cooperative Ataxia Rating Scale (ICARS) and Brief Ataxia Rating Scale (BARS)). Results: Dyskinetic scores were obtained in 79% (DIS); 65% (DIS-D) and 17% (DIS-C) versus dystonic and ataxic scores in 98% (BFMMS) and 89% (SARA/ICARS/BARS) of the children. Age-related DIS and DIS-D scores (B = −0.90 and 0.77; p  <  0.001 ) were correlated with age-related BFMMS scores (B = −0.49; p   <   0.001 ; r  =  0.87; p   <   0.001 ), whereas DIS-C scores were age-independent. Ataxic scores revealed stronger age-related regression coefficients than dyskinetic and dystonic scores (4–8 years; p   <   0.05 ). Interpretation: In healthy children, comparison between physiological dyskinesia, dystonia and ataxia rating scale scores revealed: 1. inverse age-relatedness for dystonic and ataxic scores, but not for choreoathetotic scores, 2. interrelated dystonic DIS-D and BFMMS scores, 3. the strongest age-related expression by ataxic scores. In healthy children, these physiological movement disorder-like features are interpreted as an expression of the developing underlying motor centres. Highlights: In healthy children (4–16 years of age): The Dyskinesia Impairment Scale (DIS) total and dystonia (DIS-D) (sub)scales are age-related. DIS-D and BFMMS reveal similar age-related dystonia score profiles. Choreoathetosis subscale scores are sparse and age-independent. The youngest age subgroup (4–8 years) reveals stronger age-relatedness of ataxia than of dystonia rating scale scores. The unique dystonic, ataxic and choreoathetotic score profiles are attributed to the underlying development of the associated motor centres.